One‐Step Synthesis of 2, 5‐Diaminoimidazoles and Total Synthesis of Methylglyoxal‐Derived Imidazolium Crosslink (MODIC). Issue 52 (12th November 2019) - Sabbasani, Venkata R.; Wang, Kung‐Pern; Streeter, Matthew D.; Spiegel, David A.
Abstract: Here we describe a general method for the synthesis of 2, 5‐diaminoimidazoles, which involves a thermal reaction between α‐aminoketones and substituted guanylhydrazines without the need for additives. As one of the few known ways to access the 2, 5‐diaminoimidazole motif, our method greatly expands the number of reported diaminoimidazoles and further supports our previous observations that these compounds spontaneously adopt the non‐aromatic 4( H ) tautomer. The reaction works successfully on both cyclic and acyclic amino ketone starting materials, as well as a range of substituted guanylhydrazines. Following optimization, the method was applied to the efficient synthesis of the advanced glycation end product (AGE) methylglyoxal‐derived imidazolium crosslink (MODIC). We expect that this method will enable rapid access to a variety of biologically important 2, 5‐diaminoimidazole‐containing products. Abstract : Whole in one : A general method was developed for the synthesis of 2, 5‐diaminoimidazoles through a thermal reaction between α‐aminoketones and substituted guanylhydrazines. This one‐step reaction works successfully on both cyclic and acyclic amino ketone starting materials, as well as a range of substituted guanylhydrazines. The method was applied to the efficient synthesis of the advanced glycation end product (AGE) methylglyoxal‐derived imidazolium crosslink (MODIC).